The Relationship Between The Aspect Of Fluency And Other Aspects Of Quranic Reading Mastery In J-Qaf Programme A Case Study At Malacca - Nurfadilah Mohamad; Maimun Aqsha Lubis; Muhammad Mustaqim Mohd.Zarif (AENSI Publisher, 2024)
Australian Journal of Basic and Applied Sciences, 9(18) Special 2015, Pages: 1-7 SPECIAL ISSUE MPCN_Bandung 2015